Design Of Dielectric Resonator Antenna For Wireless Communication - Othman, Mohamadariff (2009)
This dissertation discussed on the design of small, compact dielectric resonator antenna (DRA) and the study on the shape of dielectric resonator (DR) for DRA as well as to enhance the bandwidth of DRA. Disertasi ini membincangkan penghasilan antenna penyalun dielektrik (DRA) yang kecil dan padat di samping kajian terhadap bentuk penyalun dielektrik (DR) bagi DRA dan peningkatan terhadap jalur lebar DRA.